(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Kidney injury and consequences will definitely grow more common due to the rise in hematologic malignancies and innovative treatments that are extending patients’ lives who have leukemia , so the study aims to evaluate some vital indicators of kidneys function , namely interleukin 18 (IL18) , Kidney Injury Molecules -1 (KIM) , urea, and creatinine in Iraqi chronic myeloid leukemia patients. Materials and Methods: In our available research, , The study was conducted in the Marjan Medical City Hospital in Babylon Governorate and the Medical City Hospital in Baghdad Governorate, where the ELISA method was used to measure the parameters for the study . The study included 60 patients with chronic myeloid leukemia (17 males and 43 females). And 30 healthy participants who do not suffer from any disease. Results: The results revealed that that there were extremely significant differences between the control group and patients in the samples examined for the kidney function test (urea, creatinine, and IL18). While there is a non-significant difference between the control group and patients in terms of kim-1 at a p-value of ≤ 0.05. The study’s findings, however, also revealed a non-significant association between age and the levels of (urea, creatinine, IL18, and kim-1), as well as between BMI and the levels of (urea, creatinine, IL18, and kim-1). Conclusion: As a conclusion that kidney damage is possible in leukemia patients, especially when chemotherapy is taken frequently and long-term.